The courage to be happy - Kishimi,Ichiro; Fumitake Koga (Tokyo: Diamond Inc, 2016)
The Courage to Be Happy by Ichiro Kishimi and Fumitake Koga is a follow-up to their earlier work, The Courage to Be Disliked, and continues exploring the principles of Adlerian psychology. The book presents a dialogue between a philosopher and a young man, similar to its predecessor, but this time the focus is on how to cultivate happiness and live a fulfilling life. The central theme is the idea that true happiness comes from living authentically and making courageous choices. The philosopher introduces the concept that happiness is not something that happens to you, but rather a result of your decisions and actions. The book emphasizes that individuals have the power to shape their own lives, regardless of their past experiences or circumstances. The philosopher encourages the young man to overcome his fears, let go of the need for external validation, and take responsibility for his own happiness. They discuss how societal expectations and a focus on self-worth tied to achievements or approval can lead to dissatisfaction and anxiety. By embracing the courage to live for oneself, the individual can experience true freedom and peace. Ultimately, the book teaches that happiness is a process that requires courage, self-acceptance, and the willingness to embrace challenges and imperfections in life. It offers practical advice on how to let go of limiting beliefs, confront personal fears, and take proactive steps toward a more meaningful and joyful existence.
The Courage to Be Happy by Ichiro Kishimi and Fumitake Koga is a philosophical guide to achieving happiness, inspired by the principles of Adlerian psychology. Presented as a dialogue between a philosopher and a young man, the book explores how happiness is a result of personal choices rather than external circumstances or validation. It challenges common beliefs about success and self-worth, advocating for a life lived authentically, free from societal pressures and fear of judgment. Through its teachings, the book encourages readers to take responsibility for their own happiness, embrace personal freedom, and develop the courage to confront challenges. Ultimately, The Courage to Be Happy offers practical wisdom for those seeking fulfillment and peace by focusing on self-acceptance, positive action, and living in alignment with one$1 (Bs true values.s
Keywords: Adlerian Psychology; Happiness; Personal Growth